(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The natural colorant was extracted from cortex phellodendri and rubia using biological enzyme and ultrasonic technology together, and the effect of biological enzyme and ultrasonic technology on natural plant dyes extract yield was discussed through absorbance values of extracted solution in this work. Also, the dyeing solution (cortex phellodendri and rubia) extracted by enzyme-ultrasonic method was found to give the highest color difference (ΔE) among dyed fabrics. It was proved through the experiment that, natural plant dyes extract yield can be increased by using biological enzyme and ultrasonic technology together, with high efficiency, energy saving and pollution dipping features. The optimized condition for dye extraction was to extract the dry cortex phellodendri and drubia at 50°C for 60 mins. with pH 4.5.